Taman Aksara: Pembelajaran Aksara Jawa Melalui Permainan Tradisional Berbasis Ajaran Tamansiswa pada Komunitas LUKU Dusun Sarekan, Canden, Kabupaten Bantul - Purnama Sari, Dyan Indah; Praheto, Biya Ebi; Andini, Dinar Westri (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
Taman Aksara has become an important strategy in introducing and preserving Indonesia's cultural heritage, namely Aksara Jawa. In the Special Region of Yogyakarta, the learning of Aksara Jawa in schools, especially through local content lessons, is still well-maintained as an effort to preserve the existence of Aksara Jawa among the Alpha generation. This community service aims to explore the teaching of Aksara Jawa using traditional games based on Tamansiswa teachings as an alternative method to introduce Aksara Jawa to children in the LUKU Community in Sarekan, Canden, Bantul Regency. The implementation of this community service involves active participation from the partners. The service activity was carried out in the LUKU Children's Community with 25 children aged between 3 and 12 years. The results of this community service show that through the traditional game of engklek, the participants were able to more easily internalize cultural values, strengthen their love for local culture, and at the same time learn Aksara Jawa in a contextual, creative, interactive, practical, and enjoyable way.